2019
DOI: 10.12659/msm.916767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Volume Hemofiltration in Critically Ill Patients: A Systematic Review and Meta-Analysis

Abstract: Background Studies have been carried out to assess the efficacy of high-volume hemofiltration (HVHF) among critically ill patients. However, it is currently unclear whether HVHF is really valuable in critically ill patients. Material/Methods Randomized controlled trials evaluating HVHF for critically ill adult patients were included in this analysis. Three databases were searched up to July 27, 2018. The relative risk (RR), mean difference (MD), and 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…A recent systematic review (4 studies) concluded with a low-level recommendation against the use of HVHF over standard doses but stated the inconsistencies in data and significant heterogeneity across studies resulted in low quality of evidence with more studies needed [33]. Conversely, a large meta-analysis of 21 studies reported a significant survival benefit with use of HVHF, especially in the subsets of patients with sepsis and ARDS [34]. The authors assessed for 2 levels of bias and judged none of the included studies to be at low risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review (4 studies) concluded with a low-level recommendation against the use of HVHF over standard doses but stated the inconsistencies in data and significant heterogeneity across studies resulted in low quality of evidence with more studies needed [33]. Conversely, a large meta-analysis of 21 studies reported a significant survival benefit with use of HVHF, especially in the subsets of patients with sepsis and ARDS [34]. The authors assessed for 2 levels of bias and judged none of the included studies to be at low risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis could demonstrate both hemodynamic improvement (lower HR and higher MAP), and lower mortality of critically ill patients, but no substantial influence on oxygenation Index or disease severity. Also, most RCTs included in the meta-analysis were not of high quality and there was no uniform observation period concerning mortality (181).…”
Section: Extracorporeal Blood Purificationmentioning
confidence: 99%
“…Continuous blood purification is a pivotal treatment strategy for renal failure in the intensive care setting 3,10–12 . Notably, recent studies revealed that in addition to the removal of waste products, other molecules, such as inflammatory mediators/cytokines, were also the targets of removal in continuous blood purification, especially high‐dose (namely high‐volume) hemofiltration, for patients with sepsis 10,11,13–20 . However, to date, the effect of continuous venous–venous hemofiltration (CVVH), as a commonly used continuous blood purification mode, on the alterations of CD4 + T lymphocyte subsets in patients with sepsis, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12] Notably, recent studies revealed that in addition to the removal of waste products, other molecules, such as inflammatory mediators/cytokines, were also the targets of removal in continuous blood purification, especially high-dose (namely high-volume) hemofiltration, for patients with sepsis. 10,11,[13][14][15][16][17][18][19][20] However, to date, the effect of continuous venous-venous hemofiltration (CVVH), as a commonly used continuous blood purification mode, on the alterations of CD4 + T lymphocyte subsets in patients with sepsis, remains unclear. The present prospective study aims to determine whether early high-dose continuous venous-venous hemofiltration (CVVH) alleviates the alterations in CD4 + T lymphocyte subsets in septic patients combined with acute kidney injury.…”
Section: Introductionmentioning
confidence: 99%